Histochemical and SEM evaluation of the neuromuscular junctions from alcoholic rats - Torrejais, M. M.; Soares, J. C.; Matheus, SMM; Cassel, F. D.; Mello, J. M.; Basso, N. A. (Churchill Livingstone, 2002)
In the present study morphological changes occurring in the neuromuscular junctions (NMJ) of the extensor digitorum longus (EDL) and soleus muscles from albino rats (Rattus norvegicus) submitted to experimental chronic alcoholism were evaluated. Seventy two male animals aged 4 months and weighing on average 400 g were divided into three groups: control, alcoholic and isocaloric. Six rats from each group were anesthetized and sacrificed after 5, 10, 15 and 18 months. The NMJ did not show detectable morphological changes in either muscle after treatment when examined by light microscopy. With respect to the dimensions, statistical analysis demonstrated a tendency to a statistically significant treatment x time interaction for the length of soleus muscle NMJ. The ultrastructural study, however, revealed that the NMJ of the soleus muscle of animals submitted to 18 months of experimental alcoholism presented important morphological alterations. Characteristically, the NMJ of these muscles is located on an elevation on the surface of the muscle fiber, presenting a regular round, oval or elliptical shape and continuous and not very deep synaptic grooves. Approximately 30% of the NMJ of alcoholic rats are irregular in shape, with the sarcolemmal elevations typical of the synapse region being flattened on at least one side, with discontinuous synaptic grooves, and deep and punctiform contacts of the synaptic buds. These data suggest that, although skeletal muscle has a greater natural resistance against the direct or indirect effects of alcohol, some submicroscopic morphological alterations are detectable in the NMJ, especially in muscles with oxidative metabolism (soleus) following long periods of ingestion of alcohol. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: neuromuscular junctions; alcoholism; rats; EDL; soleus muscles